Permainan Flashcard Dalam Melatih Perilaku Emosi Pada Anak Dengan Autisme Di SD X - Laily Nur Fitriyah; Fikri Yumna Aqila (CV. ITTC INDONESIA, 2024)
This research aims to understand flashcard games in training emotional expression for autistic children at SD X. Autistic children often face challenges in expressing emotions appropriately, which has an impact on their social interactions and emotional development. The research method used is descriptive qualitative research with a case study approach. The subjects of this research were children with autism who attended SD X, selected using a purposive sampling technique. Data was collected through direct observation during flashcard playing activities, interviews with teachers and parents, and documentation. The research results show that flashcard games can help autistic children recognize and express basic emotions, such as happy, sad, angry and afraid. This improvement in emotional expression skills also has a positive effect on their social interactions. The conclusion of this research states that flashcard games can be an effective method in training emotional expression in autistic children, especially with the support of a conducive environment and appropriate guidance from teachers and parents.